Relationships between fitness test and kicking velocity in young soccer players - Torreblanca-Martinez, V.; Gonzales-Jurado, J. A.; Ostero-Saborido, F. M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: To study the relation between fitness test and kicking velocity in young soccer players, which has not been previously studied in this group of age. METHODS: Ninety-eight Under-11 soccer players who belonged to two professional Spanish clubs and two amateur clubs were subjected to sprint test (15 and 30 meters), countermovement jump (CMJ), estimation of maximal oxygen intake (VO2max), kicking velocity test, fatigue index of jump height and anthropometrical measures. RESULTS: Kicking velocity was significantly correlated (P<0.05) with 15-m sprint (r=-0.554) and 30-m sprint (r=-0.587), CMJ height (r=0.479), VO2max (r=0.475), body mass (r=0.311) and height (r=0.529), but not with Body Mass Index (BMI) (r=-0.011) and Fatigue Index of jump height (r=-0.05). CONCLUSIONS: This study provides new data about correlations between kicking velocity and fitness test, establishing greater correlations between kicking velocity and other variables compared to other groups of age previously studied, suggesting high transferences between results in fitness test and kicking velocity.